A Comparison of Mental Health Performance Indicators in Canada - Smith, Mark; Butler, Amanda; Lesage, Alain; Kurdyak, Paul; Adair, Carol; Vigod, Simone; Jones, Wayne (International Journal of Population Data Science, 2018)
Background There is growing recognition of the need for consistent and reliable reporting on mental health and addiction (MHA) services in Canada. While there have been improvements in the area of reporting within provinces, comparable measures across provinces are often confined to hospitalization data. The aim of this project was to test the feasibility of creating MHA performance indicators that could be compared across Canadian provinces. Methods A team of scientists from five provinces collaboratively developed the following six MHA performance indicators for ages 10 and up, using hospital, emergency, physician billing and mortality data (pop. 33.2 million): Access to the same family physician for people with MHA problems First contact for MHA problems was in an emergency department Physician follow-up after hospitalization for MHA problems Rate of suicide attempts among people diagnosed with MHA problems Suicide rates among people diagnosed with MHA problems Mortality of people diagnosed with MHA problems To facilitate meaningful inter-provincial comparisons, consensus definitions and standardized analytic processes were developed. Within age groups, 95% CI’s were calculated to determine if there were significant differences across years within age bands. Results are presented in a comparative format. Findings We found similar patterns across provinces but significant variation in the absolute rates, with no province consistently best across all indicators. In general, outcomes were poor among adolescents and young adults compared to older groups. Conclusions The results of this pilot indicate the process is feasible and meaningful. Future work could include generating comparisons on a regular basis to track system improvement; development of other measures of importance to stakeholders; and the expansion of the process to other provinces and territories. To our knowledge, this is the first report of provincial teams working collaboratively to generate comparable data on the performance of mental health services in Canada.